Are we all exploiters?*. (3rd September 2020) - Ferguson, Benjamin
Abstract: This paper argues that two single‐factor accounts of exploitation are inadequate and instead defends a two‐factor account. Purely distributive accounts of exploitation, which equate exploitation with unfair transaction, make exploitation pervasive and cannot deliver the intuition that exploiters are blameworthy. Recent, non‐distributive alternatives, which make unfairness unnecessary for exploitation, largely avoid these problems, but their arguments for the non‐necessity of unfairness are unconvincing. This paper defends a two factor account according to which A exploits B iff A gains unfairly from B and either A believes that the gains he receives in the transaction wrong B, or A is culpably unaware that the gains he receives in the transaction wrong B. This account avoids the problems of non‐distributive approaches and also delivers the intuition that exploiters are blameworthy.